Wardium ponticum sp. n. (Cestoda, Cyclophyllidea, Hymenolepidoidea), a Parasite of Pratincole (Glareola pratincola) from the Black Sea Coas - Kornyushin, V.V.; Georgiev, B.B.; Greben, O.B. (Вестник зоологии, 2012)
The new species Wardium ponticum Kornyushin, Georgiev et Greben, sp. n. (Aploparksidae Mayhew, 1925) parasitic in pratincole (Glareola pratincola Linnaeus, 1766) from Bulgaria and Ukraine is described. The species is characterized by 10 aploparaksoid hooks, 9—10 mm long, and clearly differs from all congeneric species by the shape and armament of the cirrus. Приводится описание нового вида цестод семейства Aploparksidae (Mayhew, 1925) — Wardium ponticum Kornyushin, Georgiev et Greben, sp. n. от луговой тиркушки (Glareola pratincola Linnaeus, 1766) по материалу из Украины и Болгарии. Новый вид характеризуется аплопараксоидными крючьями длиной 9–10 мкм, отличается от других представителей рода формой и вооружением цирруса. We are grateful to Svetlana Bondarenko for her useful comments on the text of the manuscript. This work was carried out in the framework of the cooperative program between the Ministry of Education and Science of Ukraine and the Ministry of Education and Science of Lithuania (project nos Ì/182—2009 and N 31V—157).